Epidemiological, Biological, and Clinical Characteristics of Central Nervous System Enterovirus Infections Among Hospitalized Patients at Ibn Sina University Hospital Center in Rabat: Case Study Report (A Series of 19 Cases) - Chemsdine Echiguer; Ghizlane El Amin; Amal Zouaki; Jalila Zirar; Myriam Seffar; Chafiq Mahraoui; Hakima Kabbaj (Advances in Virology)
Enterovirus can cause central nervous system (CNS) infections ranging from meningitis to severe encephalitis. The aims of our study were to describe and develop the current epidemiological, biological, and clinical aspects of these infections as well as to enrich Moroccan data. This is a retrospective study conducted from January 2021 to March 2023, which included all patients admitted to the hospitals of Ibn Sina University Hospital Center in Rabat (Morocco) with clinical suspicion of CNS infection and positive cerebrospinal fluid (CSF) for enterovirus detected by BioFire® FilmArray® panel meningitis/encephalitis. 1479 CSF were analyzed by multiplex PCR. Enterovirus was detected in 19 patients (1.28%) with a median age of 5 years, predominantly affecting male patients (73.7%) and children (94.7%), especially those aged 2 years and older (68.4%). Fever was the most common symptom (77.8%), followed by headache (66.7%). The seasonal peak of enterovirus detection was also observed. For most patients, the CSF was predominantly lymphocytic (88.2%) with normal glycorrhachia (84.2%) and proteinorachia (73.7%). A notable proportion (10.5%) had a normal CSF cytology. Hyperproteinorachia was found in 26.3% of cases and hypoglycorrhachia in 5.3%. Blood analysis revealed a normal WBC count in 55.6% of cases, hyperleukocytosis in 33.3%, and leukopenia in 11.1%. CRP was elevated in 72.2% of cases. CNS enterovirus infections were particularly present among the pediatric population in this study. The lack of specificity in clinical and biological manifestations may sometimes suggest bacterial etiology. The widespread use of multiplex PCR can therefore provide a reliable and rapid method of detection and diagnosis.